Arabidopsis defense mutant ndr1-1 displays accelerated development and early flowering mediated by the hormone gibberellic acid. (August 2019) - Dhar, Nikhilesh; Short, Dylan P.G.; Mamo, Bullo Erena; Corrion, Alex J.; Wai, Ching Man; Anchieta, Amy; VanBuren, Robert; Day, Brad; Ajwa, Husein; Subbarao, Krishna V.; Klosterman, Steven J.
Highlights: Master defense regulator gene NDR1 is required for resistance against Verticillium. Verticillium susceptibility is marked by early flowering, reduced bolt and rosette. Untreated ndr1-1 is early flowering and Verticillium infection further accelerates it. Activated GA signaling at least partially contributes to early flowering in ndr1-1. Implications for hormonal crosstalk involving ndr1-1, a component of SA signaling. Abstract: NONRACE-SPECIFIC DISEASE RESISTANCE (NDR1 ) is a widely characterized gene that plays a key role in defense against multiple bacterial, fungal, oomycete and nematode plant pathogens. NDR1 is required for activation of resistance by multiple NB and LRR-containing (NLR) protein immune sensors and contributes to basal defense. The role of NDR1 in positively regulating salicylic acid (SA)-mediated plant defense responses is well documented. However, ndr1-1 plants flower earlier and show accelerated development in comparison to wild type (WT) Arabidopsis plants, indicating that NDR1 is a negative regulator of flowering and growth. Exogenous application of gibberellic acid (GA) further accelerates the early flowering phenotype in ndr1-1 plants, while the GA biosynthesis inhibitor paclobutrazol attenuated the early flowering phenotype of ndr1-1, but not to WT levels, suggesting partial resistance to paclobutrazol and enhanced GA response in ndr1-1 plants. Mass spectroscopy analyses confirmed that ndr1-1 plants have 30–40% higher levels of GA3 and GA4, while expression of various GA metabolic genes and major flowering regulatory genes is also altered in the ndr1-1 mutant. Taken together this study provides evidence of crosstalk between the ndr1-1 -mediated defense and GA-regulated developmental programs in plants.